(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article is an in-depth analysis of a crucial aspect of the Old English language, which is focused on the verb «Ʒieƀan». The primary objective of this piece is to comprehensively investigate and gain a deeper understanding of the usage of this verb through the lens of Transformational analysis. This methodology involves scrutinizing the various syntactical and grammatical structures that constitute a sentence, including the transformational rules that govern how sentences can be transformed from one form to another. This allows us to uncover how the verb «Ʒieƀan» was employed in Old English and how it can be interpreted by utilizing the principles of Transformational analysis. The ultimate goal of this research is to unravel the complexities of the usage of this verb in Old English, including its various inflections and its role in sentence structure and meaning. This research is an indispensable addition to the field of historical linguistics as it provides invaluable insights into the grammar and syntax of Old English. By comprehensively analyzing the usage of the verb «Ʒieƀan» through transformational analysis, this article sheds new light on the intricacies of the Old English language and its evolution over time.